A Pilot Study: Does ReMind Behavior Modification Program Alleviate Symptoms of Depression After Percutaneous Coronary Intervention? - Bai, Tiejuan; Liu, Xiaoyan; Sherwood, Gwen; Smith, Sidney C.; Shen, Xiaojun; Feng, Jing; Dong, Jianxiu; Chang, Wenhong; Wang, Jianhui (Nursing & Health Sciences, 2025)
This quasi‐experimental study examined the effect of ReMind (Resourcefulness + Mindfulness) behavior modification program on symptoms of depression (SoD) and long‐term prognosis of patients after percutaneous coronary intervention (PCI). Four groups of quasi‐experimental training were used: 12 weeks of intervention and 12 weeks of follow‐up. One hundred thirty‐two participants were allocated into the resourcefulness coaching group (RG), the mindfulness training group (MG), theReMind behavior modification program group (RMG), and the control group (CG) at a 1:1:1:1 ratio. The data were collected using related questionnaires. A mixed effects model was used to analyze data. Results revealed that after the intervention, compared to CG and RG, SoD was reduced and the long‐term prognosis improved in RMG (least square mean difference = 19.45, 76.26; least squares mean difference = 10.99, 33.92, all p < 0.01). Three months after the intervention ended, compared to CG and MG, SoD and long‐term prognosis were improved in RMG (least squares mean difference = 13.03, 53.15; least squares mean difference = 7.37, 34.19, all p < 0.05). The findings of this study provide evidence that resourcefulness coaching combined with mindfulness training can be effective in reducing SoD after PCI. Trial Registration: Chinese Clinical Trial Registry: ChiCTR2100052937